2015
DOI: 10.4174/astr.2015.88.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of central lymph node metastasis in papillary thyroid carcinoma

Abstract: PurposeThe aim of this study was to evaluate the correlation between central lymph node (CLN) metastasis and clinicopathologic characteristics of papillary thyroid cancer (PTC). In addition, we investigated the incidence and risk factors for contralateral CLN metastasis in unilateral PTC. This study suggests the appropriate surgical extent for CLN dissection.MethodsA prospective study of 500 patients with PTC who underwent total thyroidectomy and prophylactic bilateral CLN dissection was conducted.ResultsOf 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
28
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 30 publications
(39 reference statements)
8
28
1
1
Order By: Relevance
“…Neck lymph node metastasis at diagnosis was reported in nearly 90% of pediatric cases, while they were detected in 35% of adults (Zimmerman et al 1988). Other series reported lymph node involvement at diagnosis in 40-90% of pediatric cases (Newman et al 1998, Landau et al 2000, Dinauer et al 2008, Lazar et al 2009, O'Gorman et al 2010), compared to 20-50% of adults (Zaydfudim et al 2008, Ahn et al 2015 (Table 1).…”
Section: Clinical Presentationmentioning
confidence: 94%
“…Neck lymph node metastasis at diagnosis was reported in nearly 90% of pediatric cases, while they were detected in 35% of adults (Zimmerman et al 1988). Other series reported lymph node involvement at diagnosis in 40-90% of pediatric cases (Newman et al 1998, Landau et al 2000, Dinauer et al 2008, Lazar et al 2009, O'Gorman et al 2010), compared to 20-50% of adults (Zaydfudim et al 2008, Ahn et al 2015 (Table 1).…”
Section: Clinical Presentationmentioning
confidence: 94%
“…28 This difference was statistically significant (P=0.000) which in line with other studies. 29 Author concluded that ages <45 years was significantly associated with increased incidence of CLN metastasis of patients with N0 PTC.…”
Section: Discussionmentioning
confidence: 99%
“…The number of lymph nodes resected depends on a number of factors, including the unique lymph node anatomy of the patient, and the skill and experience of the surgeon. Current data conflict regarding the impact of prophylactic central lymph node dissection on surgical morbidity, disease recurrence, and RAI use [2, 57, 14, 20, 2227]. Long-term postoperative thyroglobulin levels appear similar for patients who undergo total thyroidectomy alone as compared to patients who additionally undergo prophylactic central lymph node dissection [6, 13].…”
Section: Discussionmentioning
confidence: 99%